"Krotki" Sejm - Wiatr, Jerzy J. (Warszawa : Polska Oficyna Wydawnicza "BGW", 1993)
A commentary on the "short" parliament after the election of 1991 in Poland.
Keywords: Wiatr, Jerzy J; Poland. -- Sejm; Legislators -- Poland -- Biography; Poland -- Politics and government -- 1989-